Improving Fine Motor Skills through Cutting and Sticking Activities with Colored Picture Media at RA Thoriqotun Najah Hadipolo Jekulo Kudus - Hindriani; Heni Apriani (Journal of Action Research in Islamic Education, 2025)
Improving Fine Motor Skills Through Cutting and Sticking Activities with Colored Picture Media in Group A Children of RA Thoriqotun Najah Hadipolo Jekulo Kudus in the 2020/2021 Academic Year. PKP. Semarang: PGPAUD BI, Semarang Open University. Learning videos from the Guru Pintar Online site "Children Have Difficulty Imagining When Drawing" and the success of children in learning to cut and stick with colored picture media in group A children of RA Thoriqotun Najah Hadipolo Jekulo Kudus in the 2020/2021 Academic Year are one of the motivations for researchers to make improvements to learning. Analysis of learning values ​​is the basis for pre-cycle research. This research is a Classroom Action Research that aims to improve learning outcomes in cutting and sticking using colored picture media as a means to improve learning outcomes. This research was conducted for two cycles. The process of cycle I and cycle II was carried out online via WA Group due to the Covid-19 pandemic. The results of the analysis of the formative tests of cycle I and cycle II showed an increase in the learning outcomes of 20 children. In cycle I, the percentage of success was 70% (14 children) while in cycle II it became 90% (18 children). Thus, the use of colored image media can improve the learning outcomes of Cutting and Sticking.